Financial Technology Innovation in Modernizing Zakat Payment in the Digital Era - Alief, Abdullah; Ibi Satibi (UIN Sunan Kalijaga Yogyakarta, 2024)
Research Aims: To explore how the use of fintech in zakat payment is viewed from both Islamic jurisprudential and historical perspectives. Methodology: Library research is used as the primary data collection method. Research Findings: The research concludes that the use of financial technology for zakat payments is an innovative and flexible solution grounded in ijtihad (independent legal reasoning) within Islamic jurisprudence and The use of fintech in zakat payment is a form of technology fiqh (Islamic jurisprudence related to technology) that provides functional benefits in the context of zakat. Theoretical Contribution: Research finding the discourse on Islamic jurisprudence by highlighting how financial technology can be integrated into zakat payment systems, offering a new approach to Islamic financial practices. Research limitation and implication: The use of fintech can significantly streamline zakat payments, making the process more accessible and efficient for Muslims in Indonesia.